Understanding Issue of Online Consumer Reviews (OCR): Three Theoretical Perspectives - Luo, Margaret Meiling; Li, Wan-Ping (Archives of Business Research, 2023)
Online Consumer Reviews (OCRs) or Electronic word-of-mouth (eWOM) are important for customers and businesses. For customers, OCRs help them to make purchase decisions. For businesses, it is a direct way to understand customers. In this study, we provide the definition of OCRs and review the OCRs studies in pass few years. We found three theories are useful to understand OCRs, namely, Consumer Socialization Theory (CST), Psychosocial Distance (PD), and Information Acceptance Model (IAM). We also review the studies and identify key constructs of OCRs studies and sumerzried a table that contain major OCRs studies. Research questions that are important to OCRs studies are listed. Finally we found the limitations of the current OCRs studies.